Person centred planning and care management with people with learning disabilities - Cambridge, Paul, 1952-; Carnaby, Steven (Jessica Kingsley Publishers, 2005)
This timely book provides a reflective analysis of person centred planning for people with learning disabilities, complementing policy initiatives that focus on individualised planning and service user involvement. Drawing on practical experience and research findings, the contributors explore policy and practice issues, including: advocacy and empowerment; risk management and adult protection; inter-agency and inter-professional working; ethnicity and culture; de-institutionalisation. Vivid case studies illustrate best practice in person centred planning, and the authors offer a rich variety.